As aparências enganam?: O papel da vestimenta de informantes na confiança seletiva de crianças pequenas - Páfaro, Isabella (Universidade Federal de São Carlos, 2023)
Children learn about the world, to a great extent, from the testimony of others, but they can be true or false. Recent studies have shown that even preschool aged children prefer to learn from informants who have proved to be reliable in the past, in contrast to unreliable informants. Such competence has been conventionally called selective trust or epistemic trust. However, there is also evidence suggesting that children sometimes base their decisions about whom to trust on non-epistemic bases, such as physical appearance. Following this direction, the goal of the present study was to investigate whether clothing plays a role in the selective trust of Brazilian children when learning something new. Twenty-one 6- to 7-year-old children participated in this study. An adapted version of the classic selective trust task was used. Children were randomly distributed into two conditions. During a familiarization trial, all participants watched scenes during which one actress asks two potential informants the name of a familiar object. In the first condition (C1), one informant, formally dressed, always names the objects correctly (e.g., saying “It’s a lamp!” when seeing a lamp) and the second actress, casually dressed, always gets it wrong (e.g., says a lamp is a bottle). In the second condition (C2), the formally dressed actress always mislabels the objects and the casually dressed actress always labels them correctly. During the four test trials, the third actress always asks the name of a non-familiar object and each informant provides a novel name for it (e.g., “This is a poqui!”x “This is a tego!”. No significant diference was found between C1 and C2, both with regard to participants’ initial preference to seek help, U = 35,5; p = 0,17, and to their endorsement to the labels provided by the two informants, U = 35,0; p = 0, 13. These results suggest that children show a preference for the informant with a better accuracy rate, regardless of how they are dressed.
Can appearances be deceiving?: the role of informant clothing in the selective trust of young children
Keywords: Confiança seletiva; Vestimenta; Crianças; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO::PROCESSOS PERCEPTUAIS E COGNITIVOS; DESENVOLVIMENTO